APPLICATION OF MIXING INDEX (IP) FOR THE EVALUATION OF GEL-FORMING ABILITY IN MYOFIBRIL-PROTEIN GELS OF FISH PASTES - Hens Onibala (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2010)
This study was aimed to evaluate the mixing process effectiveness of fish meat using a mixing index (Ip). Samples used were Tilapia, Oreochromis niloticus, Walleye pollack surimi, and a mixture of both. The ability of fish meat paste myofibril-protein to form gel was evaluated with a rigidity test and MHC distribution with SDS-PAGE. The results indicated that the mixing process effectiveness with salt was 3 minutes with an Ip close to 0. This was reflected by a rigidity value >MHC. Hence, this study concluded that mixing index could be used to evaluate the ability of fish meat gel formation.